Recent trends in vaccine delivery systems: A review - Saroja, CH; Lakshmi, PK; Bhaskaran, Shyamala (International Journal of Pharmaceutical Investigation)
Vaccines are the preparations given to patients to evoke immune responses leading to the production of antibodies (humoral) or cell-mediated responses that will combat infectious agents or noninfectious conditions such as malignancies. Alarming safety profile of live vaccines, weak immunogenicity of sub-unit vaccines and immunization, failure due to poor patient compliance to booster doses which should potentiate prime doses are few strong reasons, which necessitated the development of new generation of prophylactic and therapeutic vaccines to promote effective immunization. Attempts are being made to deliver vaccines through carriers as they control the spatial and temporal presentation of antigens to immune system thus leading to their sustained release and targeting. Hence, lower doses of weak immunogens can be effectively directed to stimulate immune responses and eliminate the need for the administration of prime and booster doses as a part of conventional vaccination regimen. This paper reviews carrier systems such as liposomes, microspheres, nanoparticles, dendrimers, micellar systems, ISCOMs, plant-derived viruses which are now being investigated and developed as vaccine delivery systems. This paper also describes various aspects of “needle-free technologies” used to administer the vaccine delivery systems through different routes into the human body.
Keywords: Edible vaccines; microneedles; microparticulates; needle-free delivery; TLRs; vaccine delivery systems; vaccine